2018
DOI: 10.1183/13993003.00015-2018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen multiple breath washout test for infants with cystic fibrosis

Abstract: Multiple breath washout test (MBW) with lung clearance index (LCI) as a main outcome parameter has proven to be a valuable research tool in patients with cystic fibrosis (CF) [1, 2]. Moreover, there is growing evidence of its relevance in routine clinical practice [3]. Nevertheless, some technical limitations remain that hamper its widespread use. While most of the MBW data in infants have been acquired via sulfur hexafluoride washout (SF 6-MBW), the nitrogen variant (N 2-MBW) is recommended by the European Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
(13 reference statements)
1
17
0
Order By: Relevance
“…We observed that N 2 -LCI was 8% higher in HC, similar to the 10% difference observed by Jensen et al Other investigators have not reported differences using a common FRC, but we found that this increases the observed differences in LCI. A more recent study measuring LCI in infants with CF under sedation showed higher FRC and LCI values and lower tidal volumes with the use of N 2 -MBW when compared with SF 6 -MBW (15).…”
Section: Discussionmentioning
confidence: 88%
“…We observed that N 2 -LCI was 8% higher in HC, similar to the 10% difference observed by Jensen et al Other investigators have not reported differences using a common FRC, but we found that this increases the observed differences in LCI. A more recent study measuring LCI in infants with CF under sedation showed higher FRC and LCI values and lower tidal volumes with the use of N 2 -MBW when compared with SF 6 -MBW (15).…”
Section: Discussionmentioning
confidence: 88%
“…The technical feasibility was 100% with the new device, but software systems reduced comparability of the new device configuration in measurements of FRC . Another study showed feasibility, safety, and reproducibility of N 2 MBW in CF infants, as well as possible improved performance compared with SF 6 MBW . Both of these studies lead to better ability to perform MBW in our youngest patients.…”
Section: Physiological Assessmentmentioning
confidence: 97%
“…94 Another study showed feasibility, safety, and reproducibility of N 2 MBW in CF infants, as well as possible improved performance compared with SF 6 MBW. 95 Both of these studies lead to better ability to perform MBW in our youngest patients.…”
Section: Multiple Breath Washoutmentioning
confidence: 99%
“…The lung clearance index (LCI) from the MBW test has been recently endorsed as a primary outcome measure in CF clinical trials (Kent et al, 2014). The impact of inert gas choice remains of great interest (Guglani et al, 2018;Gustafsson, Bengtsson, Lindblad, & Robinson, 2017) and nitrogen-based (N 2 ) MBW using 100% oxygen (O 2 ) continues to be advocated for this infant age group (Koucky, Skalicka, & Pohunek, 2018). Our work has focused on defining the physiological impact of 100% O 2 exposure during MBW in this age group.…”
Section: Introductionmentioning
confidence: 99%
“…These were not observed during SF 6 MBW where O 2 exposure was kept constant at 21%. Exposure to 100% O 2 led to a transient significant reduction in tidal volume (V T ), minute ventilation (V′ E ), and "respiratory drive" (mean inspiratory flow; V T in/Tin) with a concomitant increase in end-tidal CO 2 , while respiratory rate was unchanged (Koucky et al, 2018). A significant rise of the end-expiratory lung volume (EELV, i.e., FRC) by a mean of 19 ml (≈10% relative) occurred based on the cumulative difference between inspiratory and expiratory tidal volumes (V T in -V T ex) measured by the ultrasonic flow meter over the course of the N 2 washout phase.…”
Section: Introductionmentioning
confidence: 99%